2019
DOI: 10.1002/advs.201902051
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Based Nanocatalysts via a Universal Design on Cellular Structure

Abstract: and high catalytic activity, [12] which determine the practical application prospects.There are many methods for directly preparing the NM@C catalysts with controlling particle size and enhancing stability, [13] such as simple pyrolysis, [14] wet chemical methods, [15] and atomic layering deposition. [4,16] However, clear designs on the metal catalysts and carbon supports are still lacking, and their problems also limit the practical application of metal-based nanocatalysts. [17] Therefore, it is urgent to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…The estimate of mean activation energy, through various isoconversional methods with corresponding correlation coefficients for LDPE and HDPE is mentioned in Table 2 and Table 3. The determination of degradation model is carried out through masterplots Z(α) which is calculated theoretically and experimentally by Equations (1) and (2). In these equations f(a) and g(a) correspond to integral and differential form of conversion functions given in Table S2(mentioned in supporting information).…”
Section: Estimation Of Activation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The estimate of mean activation energy, through various isoconversional methods with corresponding correlation coefficients for LDPE and HDPE is mentioned in Table 2 and Table 3. The determination of degradation model is carried out through masterplots Z(α) which is calculated theoretically and experimentally by Equations (1) and (2). In these equations f(a) and g(a) correspond to integral and differential form of conversion functions given in Table S2(mentioned in supporting information).…”
Section: Estimation Of Activation Energymentioning
confidence: 99%
“…Energy supply and waste management are two critical issues faced by most of the developing economies. The increasing energy demand and improved efficiency of energy conversion process are mainly attributed to technological advancement in present decade, which is anticipated to continue as part of improvement in the living standards [1] [2] . Management of municipal waste streams depends to a large extent on the collection, transport and treatment of waste where unscientific disposal can affect environment and human health [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The surface atoms can be easily exchanged by other ions and vacancies are easily produced in 2D materials because the exposed atoms on the surface have high reactivity and have a significant effect on the physicochemical properties of the material. [28][29]30] Importantly, the highly ordered crystal favors the transfer excited charge carriers and disordered crystal promotes the separation of charge carriers. Therefore, the ZnS@ZnO nanosheet heterostructure with highly ordered ZnO core and disordered ZnS shell could have a high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, introduction of vacancies to heterostructured 2D‐ZnS@ZnO photocatalysts can further improve the photocatalytic performance. The surface atoms can be easily exchanged by other ions and vacancies are easily produced in 2D materials because the exposed atoms on the surface have high reactivity and have a significant effect on the physicochemical properties of the material . Importantly, the highly ordered crystal favors the transfer excited charge carriers and disordered crystal promotes the separation of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19] Toincrease the thermal conductivity of OPCMs, various strategies were reported for the synthesis of shapestabilized phase change materials (ss-PCMs) through immobilizing pristine PCMs into carriers, and in the same time, high thermal conductivity additiveswere introduced into thess-PCMs to enhancetheir thermal conductivity. 20 Many additives, such as metal nanoparticles, 20,21 metal foam, 22 graphite, 23 and carbon nanotubes, [24][25] exhibited significant effects in improving the thermal conductivities of ss-PCMs. Sari et al utilized carbon nanotubes (CNTs) as high-thermal conductive additives in the ss-PCM ofsilica fume/capric acid-palmitic acid (SF/[CA-PA]), and thestudyresults suggested that the thermal conductivity of SF/(CA-PA) was 0.47 W/(mÁK), which was 1.56 times higher than that of the SF/(CA-PA).…”
Section: Introductionmentioning
confidence: 99%